Clinical characteristics of respiratory syncytial virus infection in neonates and young infants - Savić Nataša; Janković Borisav; Minić Predrag; Vasiljević Zorica; Sovtić Aleksandar; Pejić Katarina; Sarajlija Adrijan; Gazikalović Slobodan (Vojnosanitetski Pregled)
Introduction/Aim. Infection with respiratory syncytial virus (RSV) occurs during the first year of life in 50% of children and 20%-40% of them have signs of lower respiratory tract infection (bronchiolitis or pneumonia). There is an increased risk for complicated course and death from RSV infection in premature infants, especially those with bronchopulmonary dysplasia (BPD) or congenital heart disease. The aim of our study was to analyze clinical characteristics of laboratory confirmed RSV infection in order to evaluate the need for preventive measures in neonates and young infants. Methods. The prospective study included children under age of 12 months admitted to our hospital in the period November 2008-March 2009 who were positive for RSV by enzyme immunoassay membrane test. The course of disease was assessed by clinical score and radiographic findings. Results. Infection with RSV was confirmed in 91 patients: 21 (23.0%) were under the age of 30 days, 37 (40.7%) were between 31-60 days, and 33 patients (36.3%) were older than 60 days (p > 0.05). The highest hospitalization rate was in January - 33 patients (36.3%; p < 0.01). Disease severity score in these age groups (AG) were: 8.4 ± 0.4 (AG 0-30 days); 9.0 ± 0.3 (AG 31-60 days) and 8.3 ± 0.3 (AG > 60 days), without statistically significant difference among the groups (p > 0.05). Clinical scores in patients with and without risk factors were 10.5 ± 0.5 and 8.3 ± 0.2, respectively (p < 0.01). Pathological radiographic findings were observed in 72 (79.1%) and complications (apnea, significant atelectasis, encephalopathy) occured in 15 (16.5%) patients. The average length of hospital stay in complicated and uncomplicated course of the disease was 9 days and 6 days, respectively (p < 0.01). Therapy in 85 (93.4%) patients included bronchodilators, while systemic glucocorticoids and oxygen therapy were used in 51 (56.0%) and 44 (48.4%) patients, respectively. Death occured in 2 (2.2%) patients, both from a high risk group (the patient with BPD and the other one with congenital heart disease and Down syndrome). Conclusion. Infection with RSV in our settings showed marked seasonal characteristics with highest hospitalization rate in January. Although the course and outcome of the disease were favorable in the majority of our patients, the need for hospitalization and administration of therapy with possible side effects warrants that general measures for prevention of respiratory infections are followed especially in the first year of life. Severe disease and death are more probable in neonates and infants with risk factors. In these children passive immunisation with specific monoclonal antibody (e.g. palivizumab) during RSV season should be considered.